Comparative evaluation of internet addiction amongst arts, commerce, engineering and medical students - Soni, Kartik; Alam, M. N.; Joshi, Prangyada R.; Kaore, Navinchandra M.; Singh, Sukhendra P. (International Journal Of Community Medicine And Public Health, 2020)
Background: With the advancement of technology across the world web and information have been interlinked. Internet is one of the channels for communication at a large platform just with a click and scrolling by fingertip. It is an impulsive disorder, which does not involve use of an intoxicating drug. When need get converted to demand we get addicted. Addiction causes depression, anger, loneliness and other medical problems too. Considering its variable use among different professionals, present study has been conducted to assess the level of addiction among young professional students of Raipur Chhattisgarh. Methods: Ethical approval for this study (N– ADMIN/261-B/2019) was provided by the institutional ethical committee Raipur institute of Medical Sciences (RIMS) Raipur on 11/07/2019. This was a cross-sectional observational study done in Raipur which included 160 (Purposive samples) students of 18-30 years from arts, commerce, engineering and medical colleges. The study duration was of two months (15 July 2019- 15 September 2019). Predesigned pretested structured questionnaire (Young’s internet addiction test) was done using multistage simple random sampling. Results: Prevalence of addiction is 65% (104/160). Mild, moderate and severe are 38% (62/160), 21.9% (35/160), 4.4% (07/160) respectively. Among severely addicted maximum 12.5% (05/160) belong to engineering stream. Conclusions: Male are more addicted than female and engineering streams are affected more severely.